Rural radio seminar proceedings - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
In May 1989 CTA held a workshop and seminar in Ouagadougou, in cooperation with Centre Interafricain d'Etudes en Radio Rurale de Ouagadougou (CIERRO) and Groupe de Recherche et d'Echanges Technologiques (GRET) on Rural Radio and Scientific and Technical I